2021
DOI: 10.1021/acs.jpcc.1c00636
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Induced Insulator–Metal Transition in Silicon Telluride from First-Principles Calculations

Abstract: Silicon telluride (Si2Te3) is a two-dimensional semiconductor with unique structural properties due to the size contrast between Si and Te atoms. A recent experiment shows that the material turns metallic under hydrostatic pressure, while the lattice structure of the metallic phase remains to be identified. In this paper, we propose two metallic phases, M1 and M2, of Si2Te3 using the evolution algorithm and firstprinciples density functional theory (DFT) calculations. Unlike the presence of Si-Si dimers in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 55 publications
0
6
1
Order By: Relevance
“…The Te 8 @(Si 38 Te 8 )-type clathrate was also obtained and quenched to atmospheric pressure from the starting Si/Te composition of 38:16. We found no evidence for the formation of any phases of SiTe and Si 2 Te 3 reported earlier from theoretical predictions. , , …”
Section: Results and Discussioncontrasting
confidence: 69%
See 3 more Smart Citations
“…The Te 8 @(Si 38 Te 8 )-type clathrate was also obtained and quenched to atmospheric pressure from the starting Si/Te composition of 38:16. We found no evidence for the formation of any phases of SiTe and Si 2 Te 3 reported earlier from theoretical predictions. , , …”
Section: Results and Discussioncontrasting
confidence: 69%
“…We found no evidence for the formation of any phases of SiTe and Si 2 Te 3 reported earlier from theoretical predictions. 5,[10][11][12]14 The F-centered clathrate Te 7+x Si 20−x (cF) was identified for the compositional mix of Si 38 /Te 16 , where it formed simultaneously with the Te 8 @(Si 38 Te 8 )-type clathrate after the hexagonal phase disappeared (Figure S2). At higher temperatures, the Te 8 @(Si 38 Te 8 )-type clathrate is favored and is retained on cooling.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…23 The recent theoretical study identified two different metallic phases of Si 2 Te 3 by using density functional theory (DFT) calculations with the evolution algorithm. 24 The study proposed that the key of the semiconductor-to-metal transition (SMT) of Si 2 Te 3 is that Te forms bonds with single Si atoms instead of bonds with Si−Si dimers, which can be observed in the semiconducting phase. However, they failed to explain why the formation of the single Si−Te bond could lead to the SMT of Si 2 Te 3 .…”
Section: ■ Introductionmentioning
confidence: 99%